Adobe Photoshop Elements 10 learn by video - Grey, Tim (Peachpit Press, 2011)
"This complete training program from Adobe Press and video2brain offers over 5 hours of high-quality video training in the fundamentals of Adobe Photoshop Elements 10. Experienced author and educator Tim Grey shares his real-world experience using Photoshop Elements in a way that follows a logical photographic workflow. Tim guides you through the Elements Organizer before introducing image editing. You'll learn how to process digital images with Adobe Camera Raw and how to use the basic and creative editing tools in the Elements Editor. Along the way, Tim points out new features like new Guided Edits and Smart Brush options. Finally, you'll learn how to share your best images quickly and easily."--Resource description page.
Title and imprint from resource description page (viewed Jan. 24, 2012)
Keywords: Adobe Photoshop elements; Photography -- Digital techniques; Image processing -- Digital techniques; Photographie numérique; Traitement d'images; Techniques numériques; digital imaging; Image processing; Digital techniques; Photography; Digital techniques; Electronic videos